2015
DOI: 10.1039/c5nr01284h
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and characterization of transferrin–gold nanoconstructs and their interaction with bio-interfaces

Abstract: Transferrin (Tf) conjugated to gold nanoparticles and clusters combine the protein's site-specific receptor targeting capabilities with the optical properties imparted by the nano-sized gold. We have described two different synthesis protocols, one yielding fluorescent Tf-stabilized gold nanoclusters (AuNCs) and one yielding Tf-stabilized gold nanoparticles that exhibit localized surface plasmon resonance. We demonstrate that the synthetic route employed has a large influence both on the gold nanostructure for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Positively charged NSs have a strong protein adsorption in biological media and can severely damage the membranes of cells. Due to this, a neutral or negative charge is preferable to avoid strong adsorption on cell membranes and/or protein adsorption [ 26 , 60 ]. Furthermore, the shape of NSs will determine to which extent the surface coverage of stabilizing molecules is uniform or not [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Positively charged NSs have a strong protein adsorption in biological media and can severely damage the membranes of cells. Due to this, a neutral or negative charge is preferable to avoid strong adsorption on cell membranes and/or protein adsorption [ 26 , 60 ]. Furthermore, the shape of NSs will determine to which extent the surface coverage of stabilizing molecules is uniform or not [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…As proteins are nanoscale biomacromolecules with unique three-dimensional structures, protein-templated Au NCs showed great potential for biomedical applications in a variety of biological conditions . Many protein molecules, such as transferrin, bovine serum albumin (BSA), and insulin, have been explored to develop fluorescent Au NCs for biosensing and imaging applications. , …”
Section: Introductionmentioning
confidence: 99%
“…13 Many protein molecules, such as transferrin, bovine serum albumin (BSA), and insulin, have been explored to develop fluorescent Au NCs for biosensing and imaging applications. 14,15 However, protein-templated Au NCs are not ready to be used for molecular receptor-specific imaging in biomedical applications. To achieve active targeting, Au NCs have been conjugated with site-specific ligands, such as aptamer, peptide, and antibody, which serve as guiding moieties to recognize tumor-related targets specifically.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been demonstrated that chitosan can be used as stabilizer and as reducing agent to synthesize gold nanoparticles, however, longer times of reaction and heating about 45–95 °C is needed, moreover, the nanoparticles synthesized do not have control in shape and size . It is very attractive to integrate nanoparticles with biological molecules such as DNA, and proteins, aminoacids, polysaccharides, and vitamins to create new materials for potential new applications in electronics, optics, genomics, proteomics, and biomedical and bioanalytical areas . However, the use of semisynthetic derivatives of these molecules could enhance the interaction between nanoparticles and the targeted molecules without loss of biocompatibility and bioactivity.…”
Section: Introductionmentioning
confidence: 99%